Pedagogy of presence: A necessary practice in school - Gomes, Élida Fernandes da Silva; Monteiro, Edenar Souza (Seven Editora, 2023)
This text is an excerpt from the master's research that aims to evaluate good practices and references on the success of the Pedagogy of Presence in the teaching-learning process in a full-time school, also known as a full-time school, located in the municipality of Várzea Grande/MT . This is a qualitative research of the case study type and the data were obtained through an interview with teachers and students of the referred school. For data analysis, categories were built in the light of Bardin (2016) and the theoretical contribution will be based mainly on Freire (1998), Costa (2001) and Almeida (2020), who discuss human relationships, based on affective education and reflective educational practices. Therefore, it was possible to observe that both teachers and students understand the correlation between affection and learning by applying the Pedagogy of Presence as constructive and positive and of influence in the teaching-learning process. We also observed that using the principles of the Pedagogy of Presence is not difficult to access. However, it is necessary for them to become aware that it is necessary to constantly review all the material that is taken to the classroom, that is, the content, as well as the speech, the discourse, and be proposed and open to constant formation and reflection of its pedagogical praxis. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-137